Platelets as a novel source of Gremlin-1: Implications for thromboinflammation (Thrombosis and Haemostasis, 2017)
Platelets mediating haemostasis-thrombosis are central players in coronary artery disease (CAD). We characterised platelets as a novel source of Gremlin-1. Platelets express Gremlin-1 like inflammatory and endothelial cells. Gremlin-1 co-localised with P-selectin containing randomly distributed α–granules under resting state, which were peripheralised following platelet activation or adhesion over fibrinogen-coated surface. Gremlin-1 release upon activation with ADP, CRP, and TRAP was detected as enhanced surface expression; also in activated platelet supernatant as detected by Western Blot following CRP activation and by ELISA upon activation with ADP, CRP, PAR-1, and PAR4 agonist. Recombinant (rh)Gremlin-1 synergistically enhanced CRP-triggered intracellular calcium mobilisation, ADP-TRAP induced platelet activation, aggregation, and thrombin-activation triggered apoptosis; also thrombus formation ex vivo. Intracellular localisation of macrophage migration inhibitory factor (MIF) and Gremlin-1 a high-affinity binding partner and functional antagonist of MIF were found in intracoronary thrombus sections from acute coronary syndrome (ACS) patients and showed moderate overlap in α-granules of platelets. Intra-platelet Gremlin-1 levels were significantly decreased in ACS patients as compared to stable CAD (n=235). rhGremlin-1 also counteracted the anti-apoptotic and anti-thrombotic effects of rhMIF on platelets. Platelet-derived-Gremlin-1 prompted monocyte migration, facilitated adhesion under static and dynamic arterial flow conditions to collagen-adherent activated platelets; supported monocyte survival against BH-3-mimetic–induced apoptosis and macrophage differentiation in monocyte-platelet co-culture system, which were counteracted upon Gremlin-1 neutralisation. Thus platelet derived Gremlin-1 might contribute to the elevated circulating levels of Gremlin-1 in ACS and serve as a thrombo-inflammatory mediator in cardiovascular pathophysiologies.
Keywords: Gremlin-1; platelets; thrombus; monocytes; acute coronary syndrome